Targeting TLR4 Signaling Pathway in Degenerative Diseases: Molecular Docking Study of Bioactive Compounds from Ramie (Boehmeria Nivea) as Anti-Inflammatory and Antioxidant Agents - Bruneitabba Billal Irawan (Jurnal Sehat Indonesia (JUSINDO), 2026)
Toll-like receptor 4 (TLR4) acts as an upstream regulator that links chronic inflammation and oxidative stress through activation of the NF-κB pathway as well as the production of reactive oxygen species (ROS), thereby contributing to the progression of various degenerative diseases. Ramie (Boehmeria nivea) kombucha is known to contain polyphenol compounds and bioactive organic acids that have the potential to act as nutraceutical agents, but the molecular mechanisms of their interaction with the TLR4 pathway are still not fully analyzed. This study used the network pharmacology and molecular docking approaches to evaluate the potential of bioactive compounds of hemp leaf kombucha in targeting TLR4 in silico. Analysis of protein networks shows that Toll-like Receptor 4 (TLR4) has a central role as the main binding protein in inflammatory pathways and oxidative stress based on the high degree of connectivity in protein–protein interaction networks. Molecular docking simulations show that all ligands are able to bind to the active site. The flavonoid compound catechin showed the most stable binding affinity with a value of −7.8 kcal/mol, followed by quercetin of −7.4 kcal/mol, while organic acid compounds such as D-glucuronic acid, gluconic acid, and citric acid were in the range of −4.8 to −5.9 kcal/mol. The stability of the ligand–receptor complex is confirmed by the Root Mean Square Deviation (RMSD) value ≤ 2 Å. The ligand–receptor interaction is dominated by the formation of hydrogen bonds and hydrophobic interactions on amino acid residues at the TLR4 binding site, which contributes to the stability of the complex.